A Case Report of Spontaneous Closure of a Posttraumatic Arterioportal Fistula - Kittaka, Hirotada (Hindawi Publishing Corporation, 2013)
As the indications for the nonoperative management (NOM) of hepatic injury have expanded, the incidence of complications of NOM has increased. Among such complications, arterioportal fistula (APF) formation is rare, although dangerous, due to the potential for portal hypertension. Embolization is performed in APF patients with clinical signs suggestive of portal hypertension. Meanwhile, no indications for treatment have been established in APF patients without symptoms, as the natural history of posttraumatic APF is not well understood. We herein report the case of a 35-year-old female with severe hepatic injury (Grade IV on the Organ Injury Scale of the American Association for the Surgery of Trauma) due to a traffic accident. Her hemodynamic state remained stable, and an enhanced CT scan obtained on admission showed no extravasation of contrast medium, pseudoaneurysm formation, or APF; therefore, NOM was selected. Although the patient's physical condition was stable, an enhanced CT scan obtained 13 days after the injury showed APF in segment 8 of the liver. Although embolization was considered, the APF was not accompanied by portal dilatation suggestive of portal hypertension; hence, strict observation was selected. Consequently, follow-up CT performed on day 58 after the injury revealed spontaneous closure of the APF.